Adsorption Properties of Hydrated and Thermally Modified Silica Gel - J. Goworek (Adsorption Science & Technology, 1985)
The adsorption process of benzene + cyclohexane mixtures on silica gel with modified surface has been studied. Silica gel was thermally modified at 473 K, 823 K and 1023 K. Another set of modified silicas was prepared by adsorption of different amounts of water on the surface. The characteristics of the silicas were established on the basis of adsorption isotherms of nitrogen at 78 K and thermogravimetric measurements. The stability of the adsorbed layer of water in the adsorption process from the liquid phase was examined by using the Karl-Fischer method. Excess adsorption isotherms of benzene from cyclohexane were discussed in terms of a theoretical formulation concerning the adsorption on heterogeneous solid surfaces. It has been found that energetical homogeneity of the silica gel surface increases from the silica gel activated at 473 K through silicas deactivated at 823 K and 1023 K to silica gels with physically adsorbed water.